Achievement Results Are Seen From Discipline, Environment and Learning Strategy - Anggraeni, Oki; Puspasari , Elsa; Triyono, Bambang; Noviyah, Khikayatun (Journal of Economic Education, 2024)
The aim of this research is to determine the influence of learning discipline, learning environment and student learning strategies on learning achievement. This research uses quantitative methods with an associative approach. The results of the research conducted show that the learning discipline variable has a negative effect on learning achievement, with significant values as follows: 0.001 < 0.05. Furthermore, based on research conducted, it is stated that the learning environment does not have a positive effect on student learning achievement with a significant value of 0.337 > 0.05. And the learning strategy variables that have been tested show that the results have a positive effect on learning achievement, with significant values as follows: 0.04 < 0.05. From the tests carried out, 30% stated that in this research, if learning achievement was not influenced by learning discipline, learning environment and learning strategies, the results would be poor.